Arautos do reino de Deus, militantes na terra: a atuação dos operários evangélicos no Sindicato dos Metalúrgicos de São Carlos e Ibaté - Oliveira, Daniele de Jesus (2011)
This study is the result of a qualitative research about the involvement of Pentecostal workers in the Union of Metalworkers of San Carlos and Ibaté. From the religious affiliation and its guidelines is analyzed the trajectories of acquaintance and engagement with the militancy and the extent to which Christian values on the one hand and the demands of trade union struggle, others do not conflict. Among the workers interviewed, the majority showed affinity with union militancy, understanding the role of the Union is to ensure the rights of workers, hence the active participation in activities promoted by the entity. Such experiments allow us to think about the changes in behavior among evangelicals in relation to micro-and macro-social policy and its consequences. Meanwhile, religion acquires a relevant role in establishing a network of contact between them within the church and labor, leading them to become interested by the union due to the participation of some "fellow believers" militants. The result is a movement of exchange of experiences between two seemingly opposite areas on the basis of an ideological nature, but in our case has been overcoming this dichotomy between sacred world and the secular world.